Ответы и объяснения

  • ARCS
  • почетный грамотей
2011-11-20T13:08:04+00:00

16/3х - 1 = 11/9

16/3х = 11/9 + 9/9

16/3х = 20/9

4/3х = 5/9

х = 3,75/9 = 375/900 = 5/12

Ответ: х = 5/12.

 

18/49 : х = 6/35

х = 18/49 : 6/35

х = 18/49 * 35/6 = 630/294 = 15/7 = 2 1/7.

Ответ: х = 2 1/7.

Лучший Ответ!
2011-11-20T13:13:10+00:00

1) 5 1/3x - 1 = 1 2/9

16/3x = 1 2/9 + 1

16/3x = 20/9

x = (20/9) ÷ (-16/3)

x = 20/9 · 3/16

x = 5/12

 

2) 18/49 ÷ x = 6/35

x = 6/35 ÷ 18/49

x = 6/35 · 49/18

x = 7/15